Soteriologi Paulus dan Tantangan Gereja Kontemporer: Telaah Teologis dan Implementasinya bagi Umat Kristen Masa Kini - Mozes Lawalata (KHARISMATA: Jurnal Teologi Pantekosta, 2025)
The doctrine of salvation (soteriology) constitutes the central focus of preaching and teaching within the New Testament, particularly in the writings of the Apostle Paul. A robust and accurate understanding of salvation carries profound theological implications for both the church and individual believers. Nevertheless, this doctrine has often been subject to distortion in both its conceptual formulation and practical application. Certain churches are inclined toward legalism, while others fall into antinomianism, thereby neglecting the ethical demands of the gospel. This study seeks to examine Pauline soteriology through a theological lens and to assess its continuing relevance for contemporary Christian life and practice. The research employs a qualitative literature review of theological and biblical scholarship that centers on Paul’s epistles. In addition, an exegetical methodology is utilized to interpret selected key passages, specifically from Romans, Galatians, and Ephesians, in order to elucidate Paul’s understanding of salvation. The findings indicate that salvation is grounded in the unmerited grace of God, appropriated through faith in Christ, independent of human works, and inherently involves the transformation of life through the agency of the Holy Spirit. Misrepresentation of this doctrine may result in significant deviations within ecclesial life, manifesting either as rigid legalism or as an abuse of Christian freedom. Consequently, the church must intentionally cultivate a biblically grounded soteriological framework that fosters both theological soundness and consistent ethical living. The study concludes that Pauline soteriology remains theologically indispensable and practically pertinent in addressing the doctrinal and ministerial challenges confronting the contemporary church.     Doktrin keselamatan (soteriologi) merupakan inti pemberitaan dan pengajaran Perjanjian Baru, khususnya dalam tulisan Rasul Paulus. Pemahaman yang benar mengenai keselamatan berdampak besar bagi gereja dan umat Kristen. Namun, doktrin ini kerap mengalami distorsi, baik secara konseptual maupun praktis. Beberapa gereja cenderung jatuh dalam legalisme, sementara yang lain terjebak dalam antinomianisme yang mengabaikan dimensi etis Injil. Artikel ini mengkaji soteriologi Paulus secara teologis dan mengevaluasi relevansinya bagi umat Kristen masa kini. Tema-tema utama diidentifikasi melalui studi kepustakaan terhadap karya teologis dan biblikal yang berfokus pada surat-surat Paulus. Metode analisis eksegetis digunakan untuk menafsirkan teks-teks kunci, seperti Roma, Galatia, dan Efesus, guna menelusuri pemahaman Paulus tentang keselamatan. Hasil kajian menunjukkan bahwa keselamatan berakar pada anugerah Allah, diterima melalui iman kepada Kristus, bukan perbuatan manusia, dan mencakup pembaruan hidup oleh karya Roh Kudus. Distorsi terhadap doktrin ini dapat memicu penyimpangan, baik dalam bentuk legalisme maupun kebebasan yang tidak bertanggung jawab. Karena itu, gereja perlu menanamkan pemahaman soteriologis yang sehat, berakar pada ajaran Alkitab, dan membentuk kehidupan etis yang konsisten.